Acupressure for persistent cancer-related fatigue in breast cancer survivors (AcuCrft): a study protocol for a randomized controlled trial - Zick Suzanna; Wyatt Gwen; Murphy Susan; Arnedt J; Sen Ananda; Harris Richard (BMC, 2012)
Abstract Background Despite high levels of clinically significant persistent cancer related fatigue in breast cancer survivors few treatments are currently available and most pose a significant burden on the part of the woman. Acupressure, a component of Traditional Chinese Medicine, has been shown to decrease fatigue levels by as much as 70% in cancer survivors while being inexpensive, non-toxic and an easy to use intervention. The primary aim of this study was to determine the efficacy of two types of self-administered acupressure (relaxation acupressure and stimulating acupressure), compared to standard of care on fatigue severity. Secondary aims were to evaluate the efficacy of two types of acupressure on sleep and kinetic parameters required for implementation of acupressure in a clinical setting; The purpose of this paper is to share the methodology used including challenges and insights. Methods/design This study is a three group, randomized clinical trial. 375 breast cancer survivors at least 12 months after completion of cancer treatments, with moderate to severe persistent fatigue, are being randomized to one of 3 groups: self-administered relaxation acupressure; self-administered stimulating acupressure; or standard of care. Participants are assessed at baseline, 3 weeks, and 6 weeks followed by a 4-week follow-up period. The primary aim is to examine the effect of 6-weeks of relaxation acupressure compared to stimulatory acupressure or standard of care on fatigue as assessed by: weekly self-report using the Brief Fatigue Inventory; objective daytime physical activity on actigraph; or fatigue patterns assessed 4-times daily using a visual analog scale. Secondary endpoints include depression, anxiety, self-efficacy, and sleep quality. Discussion This study has the potential to develop a low-cost, self-care intervention for the most troubling of late-term effects in breast cancer populations, fatigue. The methods used may lend constructive ideas to other investigators working with this population and/or intervention. Trial registration ClinicalTrial.Gov Trials Register NCT01281904